2015
DOI: 10.1177/0363546514563904
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Combined Prevalences of Anatomic Factors Associated With Recurrent Patellar Dislocation

Abstract: Recurrent patellar dislocation is associated with an increased prevalence of patella alta, increased TT-TG distance, rotational deformity, and trochlear dysplasia compared with patients with no histories of patellar dislocation. Multiple anatomic factors were identified in the majority of patients with recurrent dislocation. Further research may identify which factors play a greater role in patellar stability and may allow physicians to predict which first-time dislocation patients are more likely to sustain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
234
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 247 publications
(254 citation statements)
references
References 28 publications
7
234
1
5
Order By: Relevance
“…К ло-кальным статическим факторам относят состояние кости, гиалинового хряща и связок, а к локальным динамическим -мышц, окружающих надколенник. Сре-ди этиологических факторов важную роль играют дисплазия мыщелков бедренной кости и дисплазия надколенника (53-71%), нарушение положения надколенника (patella alta -«высокий» надколенник») и дисплазия четырёхглавой мышцы бедра (60-61%), генерализованная гипермобиль-ность суставов (24%) [47].…”
Section: Etiopathogenic Bases For Patellofemoral Arthritis Developmentunclassified
See 1 more Smart Citation
“…К ло-кальным статическим факторам относят состояние кости, гиалинового хряща и связок, а к локальным динамическим -мышц, окружающих надколенник. Сре-ди этиологических факторов важную роль играют дисплазия мыщелков бедренной кости и дисплазия надколенника (53-71%), нарушение положения надколенника (patella alta -«высокий» надколенник») и дисплазия четырёхглавой мышцы бедра (60-61%), генерализованная гипермобиль-ность суставов (24%) [47].…”
Section: Etiopathogenic Bases For Patellofemoral Arthritis Developmentunclassified
“…При данном патологическом состоянии проблема с нестабильностью именно КС не является ведущей, поэтому коррекция про-изводится при её необходимости и обосно-ванности [47].…”
Section: Etiopathogenic Bases For Patellofemoral Arthritis Developmentunclassified
“…The normal TT:TG distance is 2-9 mm, and it is generally accepted that a figure of >19 mm is pathological [41,42,43]. It is estimated that 42% of patients with PFJI have abnormal TT:TG distance [30]. Although TT:TG distance is regarded by many clinicians as one of the important measurements in assessing patellar instability and deciding about distal realignment procedures, our research has shown that it is not a decisive element in establishing therapeutic choices for instability [43,44].…”
Section: Clinical and Radiologic Assessment Of The Patellamentioning
confidence: 99%
“…The etiology of PFJI is multifactorial as it involves several abnormal anatomical factors such as generalized hypermobility (24%) [29], patella hypermobility (51%) [29], increased femoral anteversion (27%), core, and hip abductor weakness, abnormal knee rotation, trochlea dysplasia (53-71%), abnormal Q angle, patella alta (60-66%) [30], muscle and soft tissue imbalance, external tibial torsion, and foot hyperpronation, which have been identified in patients with recurrent patella dislocation. In a recent magnetic resonance imaging (MRI) based study, 58.3% of patients had multipleanatomic factors associated with recurrent patella dislocation [30] (Figure 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation